2019
DOI: 10.3390/coatings10010026
|View full text |Cite
|
Sign up to set email alerts
|

Design of Bioinspired Emulsified Composite European Eel Gelatin and Protein Isolate-Based Food Packaging Film: Thermal, Microstructural, Mechanical, and Biological Features

Abstract: The study focused on the elaboration and the characterization of blend biofilms based on European eel skin gelatin (ESG) and protein isolate (EPI) and the assessment of European oil (EO) incorporation effect on their properties. Data displayed that the incorporation of EPI and EO to the gelatin formulation decreased the lightness and yellowness of composite and emulsified films, respectively, compared to ESG film. Moreover, ESG films exhibited improved mechanical properties than EPI films. FTIR analysis, all i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…However, a notable increase in the Tg values was obtained for gelatin pouch inner parts, probably due to the contact between the flaxseed oil and the pouches. In this context, Taktak et al [35] noted that the Tg values of European eel oil emulsified gelatin/protein isolate blend films are higher than those of non-emulsified films. Indeed, it has been reported that Tg increases with the amount of chain stiffness and bonding, along with the crosslinking between chains and the degree of crystallinity [36].…”
Section: Physicochemical Properties Of Gelatin Pouches Related To The...mentioning
confidence: 99%
“…However, a notable increase in the Tg values was obtained for gelatin pouch inner parts, probably due to the contact between the flaxseed oil and the pouches. In this context, Taktak et al [35] noted that the Tg values of European eel oil emulsified gelatin/protein isolate blend films are higher than those of non-emulsified films. Indeed, it has been reported that Tg increases with the amount of chain stiffness and bonding, along with the crosslinking between chains and the degree of crystallinity [36].…”
Section: Physicochemical Properties Of Gelatin Pouches Related To The...mentioning
confidence: 99%
“…To date, food packaging materials made of protein sources including soybean polysaccharide/gelatin blend (Liu et al., 2020), soybean protein isolate‐based films incorporating diatomite/thymol complex (Wu et al., 2021), soy protein isolate‐based nanocomposite films (Xiao et al., 2020), whey protein isolate‐based films (Oymaci & Altinkaya, 2016), European eel skin gelatin, and protein isolate‐based packaging (Taktak et al., 2019), and zein‐based cling wraps (Vimala Bharathi et al., 2019) have been studied. Accordingly, their properties and performances have also been intensively reported.…”
Section: Common Approaches Of Different Types Of Biodegradable Materi...mentioning
confidence: 99%
“…Since composite films are an obstruction to oxygen, water, and carbon dioxide, food products' fragrance is preserved. They are therefore used in food packaging [ 169 ].…”
Section: Biodegradable Food Packaging Materialsmentioning
confidence: 99%